Tin(IV) Derivatives of N-(o-Hydroxy Substituted Benzyl) Alamines - Nagarkoti, Sangita; P. Pande, Ashutosh; Kandpal, Manju; B. Mishra, Shasti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several tin(lV) derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by alcoholysis reactions involving the interaction of tin tetraisopropoxide and the latter in 1: 1, 1 : 2 and 1: 3 molar ratios in benzene medium. The compounds thus prepared were generally obtained as coloured solids out of which those containing isopropoxy group(s) were found to be hygroscopic. All these compounds were characterized by elemental and azeotrope analyses, as well as by IR and PMR spectral measurements.